(untitled) ("Journal "U". Economy. Management. Finance.", 2024)
This study examines the relevance of the issue of the influence of organizational conflicts on the activities of civil servants. Organizational conflicts can significantly complicate the work of state and municipal structures, lead to a decrease in productivity and the quality of services provided, and also negatively affect working relationships between employees. The study of this topic will reveal the main causes of organizational conflicts.